For our children : the ethics of animal experimentation in the age of genetic engineering - Nordgren, Anders. (Value Inquiry Book Series, 2010)
This book provides an overview of different ethical views on animal experimentation. Special attention is given to the production and experimental use of genetically modified animals. It proposes a middle course between those positions that are very critical and those very positive. This middle course implies that animal experiments originating in vital human research interests are commonly justified, provided that animal welfare is taken seriously. Some animal experiments are not acceptable, since the expected human benefit is too low and the animal suffering too severe. This position is supported by an argument from species care according to which we have special obligations to our children and other humans due to special relations. The book tries to bridge the gap between animal ethics and animal welfare science by discussing various conceptions of animal welfare: function-centered, feeling-based, and those focusing on natural living. The theoretical starting-point is "imaginative casuistry." This approach stresses the role of moral imagination and metaphor in ethical deliberation, accepts a plurality of values, and recognizes the importance of case-by-case balancing. In the discussion of genetically modified animals, both intrinsic ethical concerns and animal welfare concerns are addressed.